Toward unified molecular surveillance of RSV: A proposal for genotype definition - Goya,S; Galiano,M; Nauwelaers,I; Trento,A; Openshaw,PJ; Mistchenko,AS; Zambon,M; Viegas,M (Influenza and Other Respiratory Viruses, 2020)
BackgroundHuman respiratory syncytial virus (RSV) is classified into antigenic subgroups A and B. Thirteen genotypes have been defined for RSVA and 20 for RSVB, without any consensus on genotype definition.MethodsWe evaluated clustering of RSV sequences published in GenBank until February 2018 to define genotypes by using maximum likelihood and Bayesian phylogenetic analyses and average pdistances.ResultsWe compared the patterns of sequence clustering of complete genomes; the three surface glycoproteins genes (SH, G, and F, single and concatenated); the ectodomain and the 2nd hypervariable region of G gene. Although complete genome analysis achieved the best resolution, the F, G, and Gectodomain phylogenies showed similar topologies with statistical support comparable to complete genome. Based on the widespread geographic representation and large number of available Gectodomain sequences, this region was chosen as the minimum region suitable for RSV genotyping. A genotype was defined as a monophyletic cluster of sequences with high statistical support (≥80% bootstrap and ≥0.8 posterior probability), with an intragenotype pdistance ≤0.03 for both subgroups and an intergenotype pdistance ≥0.09 for RSVA and ≥0.05 for RSVB. In this work, the number of genotypes was reduced from 13 to three for RSVA (GA1GA3) and from 20 to seven for RSVB (GB1GB7). Within these, two additional levels of classification were defined: subgenotypes and lineages. Signature amino acid substitutions to complement this classification were also identified.ConclusionsWe propose an objective protocol for RSV genotyping suitable for adoption as an international standard to support the global expansion of RSV molecular surveillance.